2008
DOI: 10.1002/adfm.200800452
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand Exchange Route to Highly Luminescent Surface‐Functionalized ZnS Nanoparticles and Their Transparent Polymer Nanocomposites

Abstract: A facile ligand exchange approach for surface‐functionalized ZnS nanoparticles (NPs) with 5‐(2‐methacryloylethyloxymethyl)‐8‐quinolinol (MQ) is described. The MQ–ZnS NPs, with a cubic crystal structure, have the same diameter as ZnS NPs without MQ about 3.0 nm. The MQ–ZnS NPs exhibit strong fluorescence emission at about 500 nm and a high photoluminescence (PL) quantum yield (QY), up to 40%, with a decreasing ratio of MQ to ZnS NPs. The PL decay study reveals that the lifetimes of the different MQ–ZnS NPs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…in mesoporous silica, the solvent molecules still can penetrate into the channel of mesopores and quench the fluorescence of Znq 2 complex owing to their interaction. So the unexpected optical properties of HQ-ZnS-CMS may be attributed to the unconventional metaloquinolate complexes formed on the spherical surface of ZnS NPs in CMS with a steric confinement effect, which can reduce the attack of solvent molecules [46]. The lifetime decay dynamics of different hybrid samples were also studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in mesoporous silica, the solvent molecules still can penetrate into the channel of mesopores and quench the fluorescence of Znq 2 complex owing to their interaction. So the unexpected optical properties of HQ-ZnS-CMS may be attributed to the unconventional metaloquinolate complexes formed on the spherical surface of ZnS NPs in CMS with a steric confinement effect, which can reduce the attack of solvent molecules [46]. The lifetime decay dynamics of different hybrid samples were also studied.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, it has been shown that the HQ molecules can coordinate with the surface metal atoms of ZnS semiconductor NPs to form stable highly fluorescent hybrids. There may be a cooperative interaction of the optical properties between the semiconductor NPs and the unconventional metaloquinolate complexes formed on the spherical NPs surface with a steric confinement effect [46]. In this paper, we provided a facile strategy for the preparation of highly fluorescent ZnS-mesoporous silica hybrid NPs.…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16][17] Therefore, the theories and methods of coordination chemistry, typically molecular orbital theory and ligand field theory, can be applied to predict, design, and discuss the properties of surface complexes. On the other hand, the NC surface may provide coordination fields that differ from those of normal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…plastics was investigated [391][392][393] A further elegant route to surface-functionalized ZnS nanoparticles (NPs) to be embedded in polymer matrix was based on a facile ligand exchange approach of mercaptoethanol with 5-(2-methacryloylethyloxymethyl)-8-quinolinol (MQ) [278]. By exploiting in situ bulk polymerization, the functionalised MQ-ZnS NPs were successfully incorporated into the polymer matrix to fabricate transparent bulk nanocomposites with good thermal stability and processability.…”
Section: Zinc Sulphidementioning
confidence: 99%
“…The ligand exchange between the existing ligand and a new one is generally based on a two-step stripping route in which the existing ligand is replaced by the new once, typically displaying higher affinity and stronger binding to the targeted surface. Ligand exchange [6,195,211,222,240,251,255,[275][276][277][278][279][280][281][282][283][284] is required to replace insulating organic surfactants and allow charge transport in nanocrystal solids as well as to prepare water-soluble nanocrystals that target specific cellular sites.…”
Section: Nanocrystal-ligand Interactions and Ligands Exchange Dynamicsmentioning
confidence: 99%